Mutation of SH2B3 (LNK), a Genome-Wide Association Study Candidate for Hypertension, Attenuates Dahl Salt-Sensitive Hypertension via Inflammatory Modulation. Issue 5 (May 2015) - Rudemiller, Nathan P.; Lund, Hayley; Priestley, Jessica R.C.; Endres, Bradley T.; Prokop, Jeremy W.; Jacob, Howard J.; Geurts, Aron M.; Cohen, Eric P.; Mattson, David L.
<x xml:space="preserve">Abstract</x> Human genome-wide association studies have linked SH2B adaptor protein 3 (SH2B3, LNK) to hypertension and renal disease, although little experimental investigation has been performed to verify a role for SH2B3 in these pathologies. SH2B3, a member of the SH2B adaptor protein family, is an intracellular adaptor protein that functions as a negative regulator in many signaling pathways, including inflammatory signaling processes. To explore a mechanistic link between SH2B3 and hypertension, we targeted the SH2B3 gene for mutation on the Dahl salt-sensitive (SS) rat genetic background with zinc-finger nucleases. The resulting mutation was a 6-bp, in-frame deletion within a highly conserved region of the Src homology 2 (SH2) domain of SH2B3. This mutation significantly attenuated Dahl SS hypertension and renal disease. Also, infiltration of leukocytes into the kidneys, a key mediator of Dahl SS pathology, was significantly blunted in the Sh2b3em1Mcwi mutant rats. To determine whether this was because of differences in immune signaling, bone marrow transplant studies were performed in which Dahl SS and Sh2b3em1Mcwi mutants underwent total body irradiation and were then transplanted with Dahl SS or Sh2b3em1Mcwi mutant bone marrow. Rats that received Sh2b3em1Mcwi mutant bone marrow had a significant reduction in mean arterial pressure and kidney injury when placed on a high salt diet (4% NaCl). These data further support a role for the immune system as a modulator of disease severity in the pathogenesis of hypertension and provide insight into inflammatory mechanisms at play in human hypertension and renal disease.